Cognitive development in breast cancer patients treated with chemotherapy (2016)
Objective To evaluate the cognitive processes in patients with breast cancer during and after chemotherapy. Method A comparative study was conducted in which an assessment was made of processing speed, attention, memory, and executive functions in 14 women after receiving chemotherapy treatment and in 14 healthy women. Results The results show significant differences in the memory process, specifically in the evocation and working memory. No significant differences were found in the depression and anxiety scales. Conclusions Patients with breast cancer and received treatment with chemotherapy had a lower performance in the verbal memory process compared to the control group, as well as a significant number of intrusions, which suggests involvement in this process. © 2016 Sociedad Mexicana de Oncología